(untitled) (Fiep Bulletin - online, 2014)
Over the years Brazilian swimmers have had considerable success in international events, likely as a result of phenotype and genetic situations. The purpose of this descriptive case study was to analyze the genetic potential of a world recorder holder between generations (grandparents n = 3, parents n = 2 and the athlete n = 1), and associate phenotype characteristics through social representations learned in the family environment. As measuring instrument we used the dermatoglyphic method, through fingerprint analysis and a semi-structured interview, whose content was analyzed by the Alceste program. The genetic characteristics show that the 1st generation had a profile of coordination and endurance; the 2nd of speed and endurance and the 3rd of speed. Satisfaction and the possibility of world recognition are representations observed in the family group, which lead us to conclude that talent developed in swimming owes to predisposed generational genetics and to social stimulation experienced within the family.